Transparência e accountability em portais brasileiros - Rêgo, Herbert de Oliveira (2021)
From the Brazilian Access to Information Act (Lei de Acesso à Informação – LAI) the public transparency movement arose in Brazil creating more space to public transparency instead of public opacity. However, this movement in itself is not enough to consolidate citizenship and democracy. For that, it is essential for citizens to be able to exercise public accountability. That being said, the purpose of this thesis is to identify to what extent transparency portals in Brazilian State capitals and the Federal District (Distrito Federal) meet the features that allow accountability to be performed. Therefore, transparency portals in Brazilian State capitals and the Federal District were analysed under the perspective of transparency and accountability, from data and information regarding emergency contracts as a response to COVID-19 pandemic collected by Transparência Internacional Brasil (International Transparency Brazil) with its own methodology. This is an exploratory thesis that follows a qualitative methodology. The object of study is information portals in Brazilian State capitals and the Federal District under transparency and accountability. The documentary strategy was adopted to analyse reports published by Transparência Internacional Brasil during May to August 2020. Requirements for the portals to provide conditions for the performance of accountability were categorized by Lourenço (2015). The study is based on the indiciary paradigm, which prioritises evidences or indications. The evolution of transparency of the portals under this study was observed, and an expressive development of these features was observed in the period assigned for the study. Portals of Brazilian State Capitals and the Federal District are transparent, except those of Maceió and Cuiabá, which met only 40% of Transparência Internacional Brasil methodology requirements. Four out of 26 portals of Brazilian State Capitals and the Federal District did not meet the requirements needed to perform accountability. Therefore, the majority of Brazilian State Capitals and the Federal District meet the requirements needed to perform accountability. Despite the progress in terms of meeting conditions that allow them to be considered as transparent and to perform accountability, there are still transparency portals of Brazilian State Capitals that do not enable citizens to create a critical sense of their local reality. It is important to emphasize that we are analysing transparency portals of the main municipalities of Brazil, which indicates that the improvement should be continuous and uninterrupted. In the context of COVID-19 pandemic transparency portals need to offer transparency and accountability so that citizens may be aware of the allocation of public resources in actions to fight this pandemic.